PEMBERIAN PUPUK KANDANG SAPI DAN POC NASI BASI DALAM PENINGKATAN KESUBURAN TANAH PADA GRAFTING TANAMAN ANGGUR (Vitis vinifera) DI PRE NURSERY - Saragih, Mhd Yazid Majdiy; Tarigan, Ruth Riah Ate; Ginting, Orleans (Agros Journal of Agriculture Science, 2024)
The aim of this research is to determine the application of cow manure and stale rice POC in increasing soil fertility in grafting grape plants (vitis vinifera) in the pre-nursery. This research used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatment combinations and 3 replications so that 36 plots were needed in the research. The first factor studied was the treatment of cow manure with the symbol "Y" consisting of Y0= 0 kg/plot, Y1 = 400 g/plot, Y2 = 800 g/plot, Y3 = 1200 g/plot. Factor II treatment of giving POC basih rice with symbol A consists of A0 = 0 mL/liter of water/plot, A1 = 5 mL/liter of water/plot, A2 = 10 mL/liter of water/plot. The parameters observed were plant height (cm), shoot height (cm), number of leaves (strands), number of stem segments, stem diameter (mm) and number of tendrils. The results of the research showed that the application of cow manure, POC of stale rice and the second interaction showed no significant influence on all observation parameters, namely plant height (cm), shoot height (cm), number of leaves (strands), number of stem segments, stem diameter ( mm) and number of tendrils.Key words: cow manure, POC basi rice, grape plants INTISARITujuan penelitian ini adalah untuk mengetahui pemberian pupuk kandang sapi dan POC nasi basi dalam peningkatan kesuburan tanah pada grafting tanaman anggur (vitis vinifera) di pre nursery. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK)  Faktorial terdiri dari 2 faktor dengan 12 kombinasi perlakuan dan 3 ulangan sehingga diperlukan 36 plot dalam penelitian. Faktor yang pertama diteliti adalah perlakuan pupuk kandang sapi dengan simbol “Y” terdiri dari Y0= 0 kg/ plot, Y1= 400 g/plot, Y2 = 800 g/plot, Y3 = 1200 g/plot. Faktor II perlakuan pemberian POC nasi basih dengam simbol A terdiri A0 = 0 mL/liter air/Plot, A1 = 5 mL/liter air/plot, A2 = 10 mL/liter air/plot. Adapun parameter yang diamatin adalah Tinggi Tanaman (cm), tinggi tunas (cm), jumlah daun (helai), jumlah ruas batang, diameter batang (mm) dan jumlah sulur. Hasil penelitian menunjukan bahwa pemberian pupuk kandang sapi, POC nasi basi dan interaksi kedua menunjukan pengaruh yang tidak nyata pada semua parameter pengamatan yaitu Tinggi Tanaman (cm), tinggi tunas (cm), jumlah daun (helai), jumlah ruas batang, diameter batang (mm) dan jumlah sulur. Kata kunci: pupuk kandang sapi, POC nasi basi, tanaman anggur